The fungal composition of natural biofinishes on oil-treated wood. Issue 1 (December 2017) - Nieuwenhuijzen, Elke; Houbraken, Jos; Punt, Peter; Roeselers, Guus; Adan, Olaf; Samson, Robert
Abstract Background Biofinished wood is considered to be a decorative and protective material for outdoor constructions, showing advantages compared to traditional treated wood in terms of sustainability and self-repair. Natural dark wood staining fungi are essential to biofinish formation on wood. Although all sorts of outdoor situated timber are subjected to fungal staining, the homogenous dark staining called biofinish has only been detected on specific vegetable oil-treated substrates. Revealing the fungal composition of various natural biofinishes on wood is a first step to understand and control biofinish formation for industrial application. Results A culture-based survey of fungi in natural biofinishes on oil-treated wood samples showed the common wood stain fungusAureobasidium and the recently described genusSuperstratomyces to be predominant constituents. A culture-independent approach, based on amplification of the internal transcribed spacer regions, cloning and Sanger sequencing, resulted in clone libraries of two types of biofinishes.Aureobasidium was present in both biofinish types, but was only predominant in biofinishes on pine sapwood treated with raw linseed oil. Most cloned sequences of the other biofinish type (pine sapwood treated with olive oil) could not be identified. In addition, a more in-depth overview of the fungal composition of biofinishes was obtained with Illumina amplicon sequencing that targeted the internal transcribed spacer region 1. All investigated samples, that varied in wood species, (oil) treatments and exposure times, containedAureobasidium and this genus was predominant in the biofinishes on pine sapwood treated with raw linseed oil.Lapidomyces was the predominant genus in most of the other biofinishes and present in all other samples. Surprisingly, Superstratomyces, which was predominantly detected by the cultivation-based approach, could not be found with the Illumina sequencing approach, whileLapidomyces was not detected in the culture-based approach. Conclusions Overall, the culture-based approach and two culture-independent methods that were used in this study revealed that natural biofinishes were composed of multiple fungal genera always containing the common wood staining mouldAureobasidium . BesidesAureobasidium, the use of other fungal genera for the production of biofinished wood has to be considered.